Noncanonical NF-κB Pathway Controls the Production of Type I Interferons in Antiviral Innate Immunity - Jin, Jin (2014)
Production of type I interferons (IFN-I) is a crucial innate immune mechanism against viral infections. IFN-I induction is subject to negative regulation by both viral and cellular factors, but the underlying mechanism remains unclear. We report that the noncanonical NF-κB pathway was stimulated along with innate-immune cell differentiation and viral infections and had a vital role in negatively regulating IFN-I induction. Genetic deficiencies in major components of the noncanonical NF-κB pathway caused IFN-I hyper-induction and rendered cells and mice substantially more resistant to viral infection. Noncanonical NF-κB suppressed signal-induced histone modifications at the Ifnb promoter, an action that involved attenuated recruitment of the transcription factor RelA and a histone demethylase, JMJD2A. These findings reveal an unexpected function of the noncanonical NF-κB pathway and highlight an important mechanism regulating antiviral innate immunity.